Pengawasan Partisipatif Masyarakat Dalam Pemilihan Umum Serentak Presiden/Wakil Presiden Dan Pemilihan Umum Legislatif Tahun 2019 Di Kabupaten Kapuas - Tity Yukrisna; M. Riban Satia; R. Biroum Bernadianto (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The purpose of this research is to see the supervision of elections conducted to realize the election held democratically, direct, common, used, confidential, honest, fair and quality. The success of electoral implementation is a common necessity for all people. Because only thus elected quality figures to lead the nation. The supervision of election implementation is a shared responsibility. People can conduct supervision with participatory supervision. The method of research is qualitative, data collected using methods of interview techniques, observations, and documents. Data processing is done with qualitative, which is using an interactive data analysis model. The results of the study showed: (1) The practice of participatory supervision was carried out by forming a